DETERMINAN PRODUKSI BENIH BAWANG PUTIH DI KECAMATAN SEMBALUN - Danasari, Idiatul Fitri; Febrilia, Baiq Rika Ayu; Anwar, Anwar; Mulyawati, Sri (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2023)
This research aims to describe the characteristics of farmers and seed stockmen and analyze the determinants of garlic seed production in Sembalun District. The research was conducted through observations and interviews using questionnaires to farmers and garlic seed stockmen. The qualitative analysis method was used to identify the characteristics of farmers and seed stockmen and then quantitative analysis using multiple regression to identify the determinants of garlic seed production in Sembalun District. Based on the analysis conducted on 35 respondents (30 farmers and 5 seed stockmen) there were four variables that affect the production of garlic seeds in Sembalun District, namely wet garlic production (X1), the price of garlic seeds (X2), the price of wet garlic (X3), and the price of organic fertilizer (X4). Wet garlic production (X1) and the price of garlic seeds (X2) were found to have a positive effect while the price of wet garlic (X3) and the price of organic fertilizer (X4) had a negative effect on the production of garlic seeds in Sembalun District.